Extra-phosphoric effects of super dosing phytase on growth performance of pigs is not solely due to release of myo-inositol - Lu, Hang (J Anim Sci, 2019)
Two experiments were conducted to determine the effects of myo-inositol and phytase on growth performance, plasma metabolites, and nutrient digestibility of growing pigs. In experiment 1, 96 growing pigs with average initial body weight (BW) of 26.2 kg were used in a 25-d growth performance study. Pigs were assigned to four dietary treatments with three pigs per pen and eight replicate pens per treatment in a randomized complete block design. The four treatments were control diet (CD); CD + 2 g/kg inositol; CD + 1,000 FYT/kg phytase and CD + 3,000 FYT/kg phytase. Pigs were weighed individually every week. On day 25, blood sample was collected from one pig per pen to measure plasma metabolites concentrations. In experiment 2, 16 barrows (initial BW 34.8 ± 8.2 kg) were surgically fitted with T-cannulas. Pigs were allotted to four blocks based on BW and assigned to a quadruplicate 4 × 2 incomplete Latin square design with same four dietary treatments and two periods. Ileal digesta samples were collected from each pig on days 6 and 7 of each period to determine apparent ileal digestibility (AID) of nutrients. Phytase supplementation increased final BW and average daily gain (ADG) compared with CD (P < 0.05) with no effects on average daily feed intake (ADFI) and gain to feed (G:F) was higher in 3,000 FYT/kg phytase (P < 0.05). Inositol supplementation had no effects on growth performance. Plasma myo-inositol concentration was increased by inositol supplementation, and 3,000 FYT/kg phytase increased myo-inositol in the plasma by 97.2% (P < 0.05). Plasma P concentration was increased by 1,000 or 3,000 FYT/kg phytase with no effects on alkaline phosphatase (ALP), glucose, triglycerides (TAG), calcium (Ca), and urea concentrations. Phytase supplementation reduced (P < 0.05) the phytate-P concentration in the ileal digesta and increased the digestibility of phytate-P and total P with no effects on the AID of dry matter (DM), gross energy (GE), nitrogen (N), and Ca. In conclusion, the beneficial effects of 3,000 FYT/kg phytase on feed efficiency may due to the increased release of both myo-inositol and phosphorus (P), and may not be solely due to myo-inositol release by this level of phytase.